Sampling in Forest Inventories - Chacko, V. J. (Indian Forester, 1962)
The design of a statistical sampling scheme includes decisions on the following questions: - (i) The type and size of the basic sampling units. (ii) Number of sampling units or in other words the intensity of sampling. (iii) The distribution of the units over the forest area. (iv) Method of analysis of the data. The answers to these questions require both statistical theory and experience data in the form of considerable amount of experimental sampling. The basic investigations and data needed for designing appropriate sampling procedures in forest surveys are discussed. Lack of adequate experience data relating to the forests in India is pointed out. The available data is reviewed. Based on an analysis of Mount Stuart data, the relative efficiency of different plot sizes are studied. The serial correlations were computed and the theoretical aspects of the inter-relationship between the topographic variation and the design of survey. Discussed. The necessity for conducting pilot surveys to obtain information on the pattern of variability, the efficiency of methods of measurement and operational cost is stressed.